2019
DOI: 10.1002/chem.201901537
|View full text |Cite
|
Sign up to set email alerts
|

Ditocopheryl Sulfides and Disulfides: Synthesis and Antioxidant Profile

Abstract: Symmetrical ditocopheryl disulfides (Toc)2S2 and symmetrical and unsymmetrical ditocopheryl sulfides (Toc)2S were simply prepared under remarkably mild conditions with complete control of the regiochemistry by using δ‐, γ‐, and β‐tocopheryl‐N‐thiophthalimides (Toc‐NSPht) as common starting materials. The roles of sulfur atom(s), H‐bond and aryl ring substitution pattern on the antioxidant profile of these new compounds, which were assembled by linking together two tocopheryl units, are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Very recently, the ability in the manipulation of heavy chalcogen reagents allowed the preparation of di-tocopheryl tellurides 76–78 [105] and ditocopheryl sulfides 79, 81, 83 and ditocopheryl disulfides 80, 82, 84 [106] (Figure 17). Ditocopheryl tellurides 76–78 showed, as expected, a very good inhibition rate R inh and catalytic activity inhibition times T inh as already reported in similar Te-substituted phenols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, the ability in the manipulation of heavy chalcogen reagents allowed the preparation of di-tocopheryl tellurides 76–78 [105] and ditocopheryl sulfides 79, 81, 83 and ditocopheryl disulfides 80, 82, 84 [106] (Figure 17). Ditocopheryl tellurides 76–78 showed, as expected, a very good inhibition rate R inh and catalytic activity inhibition times T inh as already reported in similar Te-substituted phenols.…”
Section: Discussionmentioning
confidence: 99%
“…However, molecular dynamic calculations showed that in the absence of a methyl group ortho to the phenolic OH, as it occurs in δ,δ-79, the intra-HB strength is further decreased (Figure 18). In other words, the additional ortho -methyl group in sulfides γ,γ-81 or β,β-83 favours conformations with the phenolic OH protons pointing toward the sulfur atom, increasing the intra-HB strength hence reducing the chain breaking antioxidant activity [106].…”
Section: Discussionmentioning
confidence: 99%
“…The ortho-hydroxy-N-thiophthalimide derivative obtained was used as common starting material for the synthesis of both compounds. Bis-δ-tocopheryl sulfide (δ-Toc) 2 S was the product of the reaction of ortho-hydroxy-N-thiophthalimide and δ-Toc in the presence of triethylamine [34], and Bis-δ-tocopheryl disulfide (δ-Toc) 2 S 2 was the result of the reaction of the ortho-hydroxy-N-thiophthalimide with bis-trimetylsilyl selenide (Me 3 Si) 2 Se [38]. Both compounds were carefully purified by silica gel flesh column chromatography, and fully characterized [34].…”
Section: Cell Viability By Trypan Blue Dye Exclusion Testmentioning
confidence: 99%
“…Administration of vitamin E reduces the development of experimental colitis in animal models [29,30], and semi-synthetic derivatives of vitamin E can also act as anti-inflammatory agents, inhibitors of nuclear factor-kappa B (NF-kB) translocation, and adjuvants in chemotherapeutic treatments [31][32][33]. The aim of this study was to investigate the protective role of natural, α-Toc and δ-Toc, and semi-synthetic, bis-δ-tocopheryl sulfide and bis-δ-tocopheryl disulfide, indicated as (δ-Toc) 2 S and (δ-Toc) 2 S 2 , respectively [34], (Figure 2), on TNFα-induced oxidative stress, and ICAM-1 and Cl-2 expression, in HT29 cells. Additionally, the relationship between the intracellular redox state and the expression of ICAM-1 and Cl-2 was evaluated in the same cells.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of sulfurated moieties are present in many organic compounds, which possess a variety of different properties. Together with their wide use in organic synthesis, sulfurated molecules find application in different fields, as pharmaceutical [1][2][3][4][5], agrochemical [6], food [7][8][9], materials and polymer chemistry [10,11]. Despite the high variety of linear and cyclic sulfurated structures, the methods for their synthesis are often limited by the availability of sulfur reagents and by the harsh conditions.…”
Section: Introductionmentioning
confidence: 99%